Efficiency Comparisons Between Example-Problem-Based Learning and Teacher-Centered Learning in the Teaching of Circuit Theory. (24th August 2015) - Jalani, Noor Hisham; Sern, Lai Chee
Abstract: Two students can achieve the same performance in a test, but with different levels of mental effort in their respective learning phases. Thus, the combination of mental effort and performance can determine the efficiency of learning, where high efficiency is associated with high performance and low mental effort, while low performance alongside high mental effort is considered to be of low efficiency. An experimental study with pre-test and post-test designs was conducted to investigate the effects of Example-Problem-Based Learning (EPBL) in Circuit Theory teaching and learning on Malaysian first year vocational diploma students' performance and mental efforts as well as their efficiencies. The experiment was carried out for eight weeks on 38 students. The EPBL was used in the experimental group, while the existing teaching method based on Teacher-Centered Learning (TCL) is maintained for the control group. The students completed the Circuit Theory Performance Test and the 9-Point Mental Effort Rating Scale. The findings of this study indicated that EPBL enhances the students' test performances with less mental effort invested during their learning phase and hence, increases the 2-dimensional (2-D) instructional efficiency index in the learning of Circuit Theory.